Jawabanmu

2014-06-24T21:52:23+07:00
X-2y=5    ⇒x2   = 2x-4y=10     
2x+3z=12 ⇒ x1 =2x+3z=12
                          -------------- - ⇒ -4y-3z=-2
-4y-3z=-2 ⇒x1= -4y-3z=-2
y+2z=3 ⇒x4   = 4y+8z=12
                        --------------- + ⇒5z=10, z = 2
2x+3z=12              x-2y=5                 
2x+3(2)=12            3-2y=5                  x+y+z = 3-1+2 = 4 (E)
2x+6=12               -2y=2
2x=6                       y=-1
x=3
2014-06-24T21:59:03+07:00
X - 2y = 5 |x2| 2x - 4y = 10
2x + 3z = 12 |x1| 2x + 3z = 12 (_)
-4y - 3z = -2


y + 2z = 3 |x4| 4y + 8z = 12
-4y - 3z = -2 |x1| -4y - 3z = -2 (+)
5z = 10
z = 2
y + 2(2) = 3
y = 3-4
y = -1

x - 2y = 5
x - 2(-1) = 5
x = 5 - 2
x = 3

x + y + z = 3 + (-1) + 2 = 4
makasi kak :)
iya sama-sama, maaf ya klo berantakan smg bisa membantu